2013
DOI: 10.1002/jgrb.50159
|View full text |Cite
|
Sign up to set email alerts
|

The tidal displacement field at Earth's surface determined using global GPS observations

Abstract: [1] We investigate the 3-D tidal displacement field on Earth's surface recorded globally by 456 continuous global positioning system (GPS) stations of IGS spanning 1996-2011, for eight principal diurnal and semidiurnal tidal constituents. In-phase and quadrature amplitudes of the residual tidal displacements, after removal of an a priori body tide model, are estimated using the precise point positioning (PPP) technique on the daily GPS data; the resultant daily estimates are combined to derive final estimates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 70 publications
(114 reference statements)
2
47
0
Order By: Relevance
“…Therefore, kinematic PPP GPS may be used to validate and discriminate between OTL and EBT models at these accuracy levels in geophysical studies. Previous studies [e.g., Yuan and Chao , ; Yuan et al ., ] have reported an RMS ~0.4–0.5 mm M 2 height agreement between parameterized GPS harmonic displacements and geophysical models, whereas this study demonstrates both an improved accuracy and also the use of truly independent validation data, i.e., without using any geophysical models whose quality is later desired to be tested. We also obtain a periodic displacement accuracy better than the previously reported M 2 height displacement accuracies obtained using kinematic GPS, which were typically 1–5 mm in amplitude and 0–10° in phase, based on comparisons with GPS harmonic displacements or geophysical models [e.g., Khan and Tscherning , ; Khan and Scherneck , ; King , ; Yun et al ., ; Melachroinos et al ., ; Vergnolle et al ., ; Ito et al ., ].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Therefore, kinematic PPP GPS may be used to validate and discriminate between OTL and EBT models at these accuracy levels in geophysical studies. Previous studies [e.g., Yuan and Chao , ; Yuan et al ., ] have reported an RMS ~0.4–0.5 mm M 2 height agreement between parameterized GPS harmonic displacements and geophysical models, whereas this study demonstrates both an improved accuracy and also the use of truly independent validation data, i.e., without using any geophysical models whose quality is later desired to be tested. We also obtain a periodic displacement accuracy better than the previously reported M 2 height displacement accuracies obtained using kinematic GPS, which were typically 1–5 mm in amplitude and 0–10° in phase, based on comparisons with GPS harmonic displacements or geophysical models [e.g., Khan and Tscherning , ; Khan and Scherneck , ; King , ; Yun et al ., ; Melachroinos et al ., ; Vergnolle et al ., ; Ito et al ., ].…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, Yuan et al [2009] obtained M 2 height RMS agreements of around 1 mm with predictions from the NAO.99b model for 12 sites around Hong Kong, while Yuan and Chao [2012] demonstrated M 2 height RMS residuals of around 0.5 mm for over 600 sites in western USA with spatial coherence, after modeling in the GPS processing both EBTs and OTL using the FES2004 ocean tide model. Yuan et al [2013] extended this to the global scale, finding M 2 height RMS agreements (with FES2004) of 0.4 mm for 307 inland sites with continental-scale spatial coherence, and suggested that GPS harmonic displacement parameters may potentially be estimated with sufficient accuracy to provide constraints on the internal structure of the Earth. However, common to all these studies is the lack of quality control of the GPS tidal displacements with modeled values; in no case have truly independent accuracy assessments been performed to ensure geophysical interpretation can be carried out with confidence.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Rotational tidal errors can therefore appear only as aliases of subdaily EOP model defects in 24 h (and longer arc) GNSS results. The IERS model for the body tide is thought to be accurate to about 1 mm [Petit and Luzum, 2010], but in their empirical study of tidal displacements using GPS, Yuan et al [2013] inferred sensitivity to errors in the body tide down to the 0.24 mm level (vertical) that indicate lateral heterogeneities in the Earth's rheology. Ocean tidal loading magnitudes reach up to about 10 cm vertically, maximum, with the largest errors expected in areas adjoining mainly shallow seas where the global ocean tide models are least accurate or where tide heights are most extreme, such as around Brittany and coastal Antarctica.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Yuan and Chao [] and Yuan et al [] reported spatially coherent residuals between GPS‐inferred and forward modeled OTL‐induced surface displacements across a global distribution of sites located more than 150 km inland of the coast, where the influence of errors in the ocean tide models is significantly diminished. The regional‐scale spatial coherency was interpreted to indicate possible deficiencies in the adopted SEBT model.…”
Section: Introductionmentioning
confidence: 99%